Formação de professores de geografia e materiais didáticos - Albuquerque, Lilian de Souza (2010)
This present work had as its aims to check about geography teachers in São Paulo, and at the same time verify how their pedagogical materials are used in their graduation. The research had MEC data to give aspects of the Universities, also its office graduation about their own structures that are offered in these courses to graduate geography teachers. Some interviews were done with the coordinators of some these courses which made possible a well done research also in these institution. The research showed that many points get in fluency in teacher s graduation, and the pedagogical support like materials are very important for these graduations. The institutions which were researched as their coordinators say make the possible to offer a very high quality graduation for the future teachers, but some questions like how long a geography course take (it was the most important question), structures conditions, social-economical situation of the students and future geography teachers, many other reasons make good or bad influence to graduate geography teachers